Identification of Phytoplankton Diversity at Cengkrong Tidal Creek, Trenggalek, East Java, Indonesia - Andhani, Titis Dwi (Journal of Environmental Engineering and Sustainable Technology, 2025)
Phytoplankton is a key component that acts as a primary producer and bioindicator of changes in water quality. This study aims to identify phytoplankton species in Cengkrong Tidal Creek, Trenggalek, Indonesia. Sampling was conducted for six weeks at three stations representing the estuarine gradient. Parameters analyzed included phytoplankton abundance diversity index (H'), dominance index (D), and water parameters such as temperature, dissolved oxygen, pH, salinity, nitrate, and orthophosphate. The results of the study found five phytoplankton phyla, consisting of Bacillariophyta (70%), Chlorophyta (18%), Cyanophyta (6%), Dinoflagellates (3%) and Charophyta (3%). The Bacillariophyta phylum found 23 genera, Chlorophyta phylum found 6 genera, Cyanophyta phylum found 2 genera, Charophyta phylum found one genus, namely Mougeotia. The Dinoflagellate phylum found one genus, namely Amphidinium. The H' value ranges from 0.51 to 2.38, indicating low to moderate levels of diversity, while the D value ranges from 0.12 to 0.74, indicating low to high dominance. Water quality parameters generally still support phytoplankton growth, but nitrate and orthophosphate concentrations exceed the specified quality standards. Regular water quality monitoring, as well as preventing the entry of pollution sources into the waters, is necessary to avoid phytoplankton explosions that cause a decline in ecosystem quality.